2013
DOI: 10.1007/s10815-013-0081-3
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid stimulating hormone levels rise after assisted reproductive technology

Abstract: Purpose The goal of this study was to determine whether high E2 levels after controlled ovarian hyperstimulation affect TSH. Methods Patients completing ART cycles between AprilOctober 2010 were eligible for this cohort study. 180 patients were recruited however those with known thyroid disease were excluded. The final analysis included 154 subjects. Blood was collected at each visit during the ART cycle as well as at the pregnancy test. Samples were frozen at −20°C and analyzed together for E2 and TSH using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 31 publications
(35 reference statements)
4
17
1
2
Order By: Relevance
“…In this special setting of IVF, however, caution has to be used when measuring TSH at an early time of pregnancy since blood levels of TSH and fT4 show a unique positive feedback situation with slightly elevated TSH levels. This TSH peculiarity has also been observed by other authors [21]. Parallel to this early elevation of TSH levels we also observed a reciprocal decrease of magnesium levels.…”
Section: Clinical Studies Dealing With Reference Levels For Tsh In Prsupporting
confidence: 91%
“…In this special setting of IVF, however, caution has to be used when measuring TSH at an early time of pregnancy since blood levels of TSH and fT4 show a unique positive feedback situation with slightly elevated TSH levels. This TSH peculiarity has also been observed by other authors [21]. Parallel to this early elevation of TSH levels we also observed a reciprocal decrease of magnesium levels.…”
Section: Clinical Studies Dealing With Reference Levels For Tsh In Prsupporting
confidence: 91%
“…Several independent studies have reported a significant increase in serum TSH during COH or within 1 month after COH (6,7,8,9,10,11,12). The causes of these modifications have not yet been fully clarified.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, this present study observed significantly higher TSH levels in women who were undertaking IVF treatment. There have been a few authors that have investigated the relationship between thyroid function and controlled ovarian hyperstimulation (COH) in IVF cycles and show that TSH increases significantly with a rise in oestrogen [38,39] and elevated TSH is linked to decreased fertilisation rates in those women undertaking IVF treatment [37]. The reasons as to why TSH is higher in this treatment group is uncertain, especially since these patients are undertaking fertility treatment due to a number of various underlying conditions (for example endometriosis, PCOS, male factor).…”
Section: Thyroid Function During Conception Cyclesmentioning
confidence: 99%